Series Expansions for Finite-State Markov Chains - Bernd Heidergott; Arie Hordijk; Miranda van Uitert (Tinbergen Institute, 2005)
This paper provides series expansions of the stationary distribution of a finite Markov chain. This leads to an efficient numerical algorithm for computing the stationary distribution of a finite Markov chain. Numerical examples are given to illustrate the performance of the algorithm.
Keywords: C63; C44; 330; finite-state Markov chain; (Taylor) series expansion; measure-valued derivatives; coupled processors